Algoritmo de codificação diferenciada para redes de sensores sem fio - Juliana Franca Santos Aquino (2007)
Wireless sensor network is a type of ad hoc network that can be used to monitor a variety of environmental characteristics such as sound, temperature, humidity, pressure and noise levels. A typical problem of these networks is how to collect and send historical information from allsensor nodes to the base station. Due to the resource limitations such as energy, it may be impracticable to transmit a full-resolution data feed from each sensor node. Therefore, it is necessary to minimize the communication among sensor nodes and the base station, since thatthe communication in wireless media is the primary consumer of energy. So, it is important to apply techniques for the reduction of the data so that the fewest bits can be transmitted in the wireless medium. In this master thesis, a differential coding algorithm for wireless sensor networks was considered, where sensor nodes report just the differences among their readings for a common database. The simulation results have shown that the algorithm presented a good performance in applications where sensor nodes collect similars readings over time.